Digital pseudo-random modulation: a key to EMI reduction in EVS boost converters - M'barki, Zakaria; Salih, Ali Ait; Mejdoub, Youssef; Rhazi, Kaoutar Senhaji (International Journal of Applied Power Engineering (IJAPE), 2024)
Pseudo-random position pulse modulation (RPPM) technique can be implemented either analogically using pseudo-random binary sequences (PRBS) to generate a pulse-width modulation (PWM) control signal or digitally through an Arduino Uno board. It plays a critical role in mitigating conducted electromagnetic emissions (EMI) in boost converters dedicated to electric vehicle systems (EVS) applications. The digital implementation offers a significant advantage by enabling a substantial widening of the frequency spectrum of the control signal. This expanded spectral range results in a noticeable reduction in emitted electromagnetic interference (EMI), making the digital method the preferred choice. The increased spectral bandwidth effectively mitigates EMI, which is particularly advantageous for EMI-sensitive EVS systems. In conclusion, the digital pseudo-random modulation approach, facilitated by Arduino Uno, proves to be more effective in reducing EMI in EVS boost converters. Its capability to broaden the control signal's frequency spectrum leads to a favorable reduction in emitted EMI, ultimately enhancing electromagnetic compatibility and overall system performance.